If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -2x = 79 Solving 5 + -2x = 79 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -2x = 79 + -5 Combine like terms: 5 + -5 = 0 0 + -2x = 79 + -5 -2x = 79 + -5 Combine like terms: 79 + -5 = 74 -2x = 74 Divide each side by '-2'. x = -37 Simplifying x = -37
| 0.7x-4.6=0.3 | | x/8+4=x/8 | | 2x+5/6=3x+7/6 | | 5-2x=81 | | 58.6*5= | | .50x+.60(20)=.25(102) | | 2x-2=90 | | 1/3x=-9 | | 2-2x=90 | | 2x^2-8x-165=0 | | 12x-5+3x-3=11x-2+3x | | 5(x-7)-2=-37 | | 3x-9+3x-5=12x-3+3x | | 12x^2+13x+1=0 | | 6-(4y-8)=3-5y | | 11x^2-24x-261=0 | | 1/5x-2=-2 | | y=1/5(-5)-2 | | 5-1=0 | | 40x+50y=249 | | -13-2y=-3 | | 2x+3x=400 | | x-2(4)=-3 | | (X-6)/(x+1)=0 | | 67+x=182.50 | | x(x-2)=124 | | (T/t-1)+(2/t+1)=(2/t^2-1) | | 3x+45=10x+24 | | (4x+37)=(3x+43) | | 25=X+7 | | 17=7+27t-16t^2 | | 2x^2-x=2-4x |